Selection of raw materials and main components for production of sour milk drink from goat’s milk - M. A. Gasheva (Новые технологии, 2021)
Fermented milk products are the main components of functional nutrition. In response to the increasing demand of the population for fermented milk products, industry experts strive to expand the assortment, develop the latest technologies, and create new types of fermented milk drinks. The main task of creating industrial technologies is a beneficial effect on all organs of the human body. The study of the diversity of the microflora of fermented milk products allows the development of new technologies, giving the products special functionality. Since ancient times mankind has used fermented milk products not only in nutrition, but as a remedy for many diseases. Goat’s milk satisfies the need for a qualitative and quantitative ratio of nutrients. It has unique properties due to its protein composition, such as easy digestibility of milk, therapeutic and dietary properties, natural homogenization, hypoallergenic properties. Taking into account the increased demand for the processing of goat’s milk in Russia, the development of a fermented milk drink technology is urgent. A fermented milk drink based on raw goat’s milk will differ in quality characteristics, functionality and attractiveness for consumers of all age groups of the population, if compared with similar ones made from raw cow milk. The composition and properties of goat’s milk of local breeds of goats, as the main raw material for the production of a fermented milk drink with a functional orientation, have been studied in the research. The selection of starter cultures has been carried out, the use of which contributes to the absence of a pronounced taste and aroma characteristic of dairy products from goat’s milk, and also gives functional properties to the fermented milk drink.